Posttraumatic stress disorder after a first-ever intracerebral hemorrhage in the Chinese population: A pilot study. Issue 1 (2nd January 2020) - Jiang, Che
ABSTRACT: The objective of this study was to reveal the prevalence, associated risk factors, and long-term outcomes of Posttraumatic stress disorder (PTSD) in patients after intracerebral hemorrhage (ICH). Consecutive patients admitted to our institute from January 2016 to September 2016 for a first-ever ICH were asked to participate in our study. PTSD was determined with Diagnostic and Statistical Manual of Mental Disorders (fifth edition; DSM-5), and questionnaires on mental and physical status were used. Patients were followed at 3 and 12 months after ICH. Sixty-four patients were eventually included for analysis. Compared with patients without PTSD, patients with PTSD were more likely to be female (67% vs. 29%, p  = 0.01), and had higher rates of receiving minimally invasive surgery (MIS; 47% vs. 18%, p  = 0.04). Patients with PTSD achieved higher IES-R scores, had more intense anxiety and depression, were more habitually use maladaptive coping strategies, and had poorer quality of life and worse stroke-related disability than those without PTSD. At 12-months follow-up, 6 of the 14 (43%) patients initially diagnosed with PTSD had self-recovered. ICH leads to increased PTSD risk in the Chinese population, especially those who are female, more severely disabled, or received MIS.